Parameters identification for weld quality, strength and fatigue life enhancement on HSLA (S460G2+M) using manual GMAW followed by HFMI/PIT / Dahia Andud... [et al.] - Andud, Dahia; Nordin, Norridzwan; Mat, Muhd Faiz; Saidin, Salina (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
This research is aimed to identify suitable parameters in achieving weld quality, strength and fatigue life enhancement for structural welding. The investigated material is High Strength Low Alloy Steel S460G2+M commonly used for harsh environment such as offshore structure or platform. Due to the extensive use in fabrication industry, the selected welding process is manual GMAW with filler wire ER80S-Ni1 and shielding gas 80%Ar + 20% CO2. The research initiates with the determination of suitable welding parameters such as Current, Voltage, welding speed etc. to attain good quality which refers to international welding standards AWS D1.1/D1.1M:2015. Further, the parameters of HFMI/PIT are to be investigated starting with the comparison of strength between untreated and treated tensile fatigue specimen. As the final results, the development of a conceptual WPS and PQR including HFMI/PIT-Procedure as an integrated model with regard to structural and fatigue life enhancement is presented for production purpose and for further use on application which is identical to this research.